Towards Deterministic Reconfigurable Networks - Zhou, Zikai George; Kellerer, Wolfgang (Electronic Communications of the EASST, 2021)
Compared with legacy networks, programmable networks are highly flexible and need to be reconfigured dynamically. In this early work paper, we study the fast and consistent network update which is the key enabler to realize deterministic reconfigurable networks. The reconfiguration speed is one side of the coin. The ongoing best-effort traffic cannot be interrupted during the network reconfiguration as well. In terms of reconfiguration speed, we implement and compare our method with the state-of-the-art decentralized and centralized update methods.